2015
DOI: 10.1002/eji.201445150
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 deficiency in T cells protects mice from experimental autoimmune encephalomyelitis

Abstract: NFATc1 is a member of the nuclear factor of activated T cells (NFAT) family of transcription factors. NFAT is activated upon T-cell receptor activation followed by intracytoplasmatic Keywords: CD4+ T cells r EAE r NFAT r RORγT r Th17Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionNuclear factor of activated T cells (NFAT) was originally described as a transcription factor inducing the expression of interleukin 2 (IL-2) [1]. The NFAT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…Previous studies using NFAT2 −/− /Rag-1 −/− chimeric mice likewise reported impaired proliferation of NFAT2-deficient T cells ( 38 ) but independently of autocrine IL-2 secretion. In the EAE model, NFAT2 deficiency reduced the proliferation capacity of MOG-specific T cells in IL-2-dependent and -independent manners ( 41 ). In our model, CD8 + T cells produced less IL-2 under suboptimal TCR stimulation, and NFAT2 deficiency reduced proliferation in IL-2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using NFAT2 −/− /Rag-1 −/− chimeric mice likewise reported impaired proliferation of NFAT2-deficient T cells ( 38 ) but independently of autocrine IL-2 secretion. In the EAE model, NFAT2 deficiency reduced the proliferation capacity of MOG-specific T cells in IL-2-dependent and -independent manners ( 41 ). In our model, CD8 + T cells produced less IL-2 under suboptimal TCR stimulation, and NFAT2 deficiency reduced proliferation in IL-2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…NFAT2 binding sites were found within the Il17a promoter ( 39 ) and the Il10 promoter ( 40 ). Recently, NFAT2 has been shown as a positive regulator of RORγT and Th17 cytokines during TGF-β-mediated Th17-cell differentiation ( 41 ). NFAT2-deficient TGF-β-induced iTreg cells showed a slight reduction of CD25 and Foxp3 expression as compared to WT cells ( 42 ), indicating no essential role for NFAT2 in iTreg cell development.…”
Section: Introductionmentioning
confidence: 99%
“…It is produced by T helper type 17 (Th17) cells and it is also associated with autoimmune diseases. 12 IL-17A was found upregulated in moderate to severe asthma where it contributes, e.g., to accumulation of neutrophils in the airways. 13 Schnyder-Candrian et al 14 showed that exogenous rmIL-17A during allergen challenge decreased airway hyperresponsiveness (AHR).…”
Section: Introductionmentioning
confidence: 97%
“…NFAT1, NFAT2 and NFAT4 are expressed in cells of the immune system and have important roles in T cell development and function (3). While NFAT family members make similar contacts with DNA (4), they show distinct expression patterns and functions, as judged by the non-overlapping phenotypes of mice deficient in individual NFAT family members ((5, 6) and reviewed in (7)).…”
Section: Introductionmentioning
confidence: 99%